2007
DOI: 10.1172/jci32163
|View full text |Cite
|
Sign up to set email alerts
|

CD200 is induced by ERK and is a potential therapeutic target in melanoma

Abstract: Immune-mediated antitumor responses occur in patients with metastatic melanoma (MM), and therapies designed to augment such responses are clinically beneficial. Despite the immunogenicity of melanoma, immunomodulatory therapies fail in the majority of patients with MM. An inability of DCs to sufficiently activate effector cells may, in part, underlie this failure of the antitumor response seen in most patients. In this work, we show that mutation of N-RAS or B-RAF, signature genetic lesions present in most MMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 47 publications
4
94
0
Order By: Relevance
“…[7][8][9] MAPK pathway activation in tumor cells without MAPK mutations, such as through Toll-like receptor stimulation or transforming growth factor beta signaling, can promote tumor infiltration and immune suppression at least in part via CD200 and programmed death-ligand 1 (PD-L1) induction, and these effects can be reversed by MEK inhibition. [10][11][12][13] Similar findings are reported in BRAF V600E -mutant melanoma, in which inhibition of BRAF and MEK increases T-cell recognition and dendritic cell function. 14,15 This evidence strongly supports that targeting MAPK signaling in cancer patients could reverse tumor-induced immune suppression, leading to longer disease control, improved resistance to opportunistic infections, and enhanced efficacy of immune-based therapies.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…[7][8][9] MAPK pathway activation in tumor cells without MAPK mutations, such as through Toll-like receptor stimulation or transforming growth factor beta signaling, can promote tumor infiltration and immune suppression at least in part via CD200 and programmed death-ligand 1 (PD-L1) induction, and these effects can be reversed by MEK inhibition. [10][11][12][13] Similar findings are reported in BRAF V600E -mutant melanoma, in which inhibition of BRAF and MEK increases T-cell recognition and dendritic cell function. 14,15 This evidence strongly supports that targeting MAPK signaling in cancer patients could reverse tumor-induced immune suppression, leading to longer disease control, improved resistance to opportunistic infections, and enhanced efficacy of immune-based therapies.…”
Section: Introductionsupporting
confidence: 73%
“…The above results, together with the immunophenotypic characterization, suggest that the BRAF V600E mutation might accelerate disease development in B-cell leukemia by promoting immune evasion or suppression as observed in some solid tumors, 10,[12][13][14][15]37 rather than simply by affecting proliferation or apoptosis. We therefore examined the effects of B cells expressing BRAF V600E on other immune compartments.…”
Section: Braf V600e B Cells Suppress T-cell Proliferation and Functionmentioning
confidence: 73%
“…Improved understanding of the biology of CLL may help identify other variables predicting which patients may have a poor disease outcome. We have previously shown that CD200, an immunoregulatory molecule overexpressed on a number of solid and systemic tumors, as well as cancer stem cells, played a functional role in suppressing cytotoxic killing of CD200 þ lymphoma and CLL cells (1)(2)(3)(4)(5)(6). Increased expression of CD200R, which is required for signaling mediated following CD200 engagement, was detected on a subpopulation of CD4 þ T cells in the spleen of patients with CLL relative to controls (6).…”
Section: Cd19mentioning
confidence: 98%
“…It is thought to reverse the suppression of CD200R-expressing effector cells by blocking CD200 expressed on tumors and is thus restricted to use in the case of CD200-expressing tumors. Indeed, various studies have shown that CD200-expressing tumor cells can suppress T-cell responses in vitro and in vivo (McWhirter et al, 2006;Kretz-Rommel et al, 2007;Petermann et al, 2007;Siva et al, 2008;Pallasch et al, 2009;Wong et al, 2010). Although it is not clear by which mechanism CD200 expression on tumors suppresses the immune system, in vitro studies suggest that blocking CD200-CD200R enhances Th1 responses (McWhirter et al, 2006;Siva et al, 2008).…”
Section: Introductionmentioning
confidence: 99%